2018
DOI: 10.3329/bjpsy.v29i2.37851
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with relapse of schizophrenia

Abstract: Schizophrenia is a chronic psychiatric illness with high rate of relapse which is commonly associated with noncompliance of medicine, as well as stress and high expressed emotions. The objective of the study was to determine the factors of relapse among the schizophrenic patients attending in outpatient departments of three tertiary level psychiatric facilities in Bangladesh. This was a cross sectional study conducted from July, 2001 to June, 2002. Two hundred patients including both relapse and nonrelapse cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
2
4
0
4
Order By: Relevance
“…[14] Another cross-sectional study conducted among one hundred relapse and one hundred non-relapse cases of schizophrenia who attended three psychiatry outpatient departments of Dhaka, Bangladesh presents the similar findings where non-compliance was higher among the relapse group (80.0%) than the non-relapse group (14%) and was statistically significant p=<.001. [28] in addition, similar finding was found in the study conducted among 217 schizophrenic patients in Johannesburg that showed that two-third of the study population were poor adherent to treatment in relapse with p=<.001. [10] furthermore, in a retrospective observational study conducted among 876 people of Republic of China also revealed similar findings in which 30% of respondents had negative attitudes towards medicine with 2.5times more relapse than adherent to medicine 54.5% versus 20.7%with (OR=4.602, p=<.001).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…[14] Another cross-sectional study conducted among one hundred relapse and one hundred non-relapse cases of schizophrenia who attended three psychiatry outpatient departments of Dhaka, Bangladesh presents the similar findings where non-compliance was higher among the relapse group (80.0%) than the non-relapse group (14%) and was statistically significant p=<.001. [28] in addition, similar finding was found in the study conducted among 217 schizophrenic patients in Johannesburg that showed that two-third of the study population were poor adherent to treatment in relapse with p=<.001. [10] furthermore, in a retrospective observational study conducted among 876 people of Republic of China also revealed similar findings in which 30% of respondents had negative attitudes towards medicine with 2.5times more relapse than adherent to medicine 54.5% versus 20.7%with (OR=4.602, p=<.001).…”
Section: Discussionsupporting
confidence: 85%
“…In present study, mean age of the participants in cases was 33.51±10.94 and 35.79±11.12 in control group which was higher to the cross-sectional study conducted among the one hundred relapse and one hundred non-relapse cases of schizophrenia attended in three psychiatry outpatient departments of Dhaka, Bangladesh showed 28.7±7.4 in relapse and 27.9±6.0 in nonrelapse group. [28] This study findings revealed that the low to moderate family support was greater in case 87.1% compared to 72.9% in control group and high friends support was 94.3% in control group and 64.3% in case group. High significant others support was 92.9% in control group and 60% in case group.…”
Section: Discussionmentioning
confidence: 53%
“…Haque et al . ( 2018 ) also highlighted the importance of examining the influence of multiple factors when investigating schizophrenia relapse, given that previously neglected relationships may become important in certain situations or for certain groups of people, necessitating changes to the treatment plan.…”
Section: Introductionmentioning
confidence: 99%
“…Hasil pengamatan ini didukung dengan pernyataan dari Direktur RSJ Kalimantan Barat yang mengatakan bahwa : "Jika dilihat jumlah dari penduduk Kalbar adalah sekitar 5 juta jiwa, dilihat dari indikator hasil riset menyatakan bahwa ada sekitar 5.000 penderita gangguan jiwa di Kalbar. 5.000 penderita yang teridentifikasi gangguan jiwa ini, ada 10% yang memang perlu pengangan segera karena masuk pada gangguan jiwa berat"².…”
Section: Pendahuluanunclassified
“…Dampak buruk kekambuhan bagi keluarga yaitu menambah beban keluarga dari segi biaya perawatan dan beban mental karena anggapan negatif masyarakat kepada pasien, pasien sulit diterima oleh lingkungan atau masyarakat sekitar. RSJ juga akan terbebani karena bertambahnya pasien yang dirawat 4,5 .…”
Section: Pendahuluanunclassified